Herpes Simplex Virus-2 Hepatitis: A Case Report and Review of the Literature. (21st February 2020) - Ahmed, Amna; Granillo, Alejandro; Burns, Ethan; Glassner, Kerri; Naseem, Nishath; Force, Christopher; Crumley, Suzanne M.; Drews, Ashley
Abstract : Herpes simplex virus (HSV) is a rare cause of hepatitis in pregnancy and the chronically immunosuppressed, with a high propensity to progress to acute liver failure (ALF) and death. Patients typically present with a nonspecific clinical picture that often delays diagnosis and treatment, contributing to the high mortality rate. We present a case of a young female on chronic prednisone and hydroxychloroquine for systemic lupus erythematosus (SLE) who was diagnosed with HSV-2 hepatitis after presenting with right-sided chest and abdominal discomfort. Despite early clinical deterioration, prompt initiation of therapy with intravenous acyclovir and methylprednisolone led to rapid improvement.